Аналіз небезпеки будівництва та використання гребель - Пустовіт, І. О. (ХНУРЕ, 2022)
This paper describes the features of operation of hydroelectric power plants and dams. Examples of dangerous situations related to dams are given. Statistics of harm to people and the environment are given. Written about the causes of accidents, ways to prevent situations and ways to eliminate disasters. The information on tendencies in the field of hydraulic engineering constructions in the progressive states is stated
Keywords: hydroelectric power dams; hydraulic engineering; hydraulic engineering constructions